Antioxidant and pro-oxidant activity of Vitamin C in oral environment - Aratirika Chakraborthy; Pratibha Ramani; Herald Justin Sherlin; Priya Premkumar; Anuja Natesan (Wolters Kluwer Medknow Publications, 2014)
Context: Antioxidant properties and Vitamin C. Background: Vitamin C is a naturally occurring organic compound and a potent antioxidant preventing oxidative damage to lipids and other macromolecules. It can also exhibit bimodal activity as a pro-oxidant at a higher concentration. Vitamin C has a switch over role from being an antioxidant in physiologic conditions to a pro-oxidant under pathologic conditions. A systematic review of this role would help to elucidate whether it is an antioxidant or a pro-oxidant in the oral environment. Objective: To review studies reported in the literature elucidating the activity of Vitamin C and determine whether it is an antioxidant or a pro-oxidant. Materials and Methods: Articles were searched in PubMed, MEDLINE using appropriate key words like "Vitamin C," "antioxidant activity," "pro-oxidant activity," "oral health" "oral disease." Hand search of journals was also performed. Articles were reviewed and analyzed. Results: Search strategy reviewed 10 relevant articles which studied the dual role of Vitamin C. 65% of authors analyzed antioxidant action of ascorbic acid compared to 35% of the pro-oxidant potential. Vitamin C acts as an antioxidant and a pro-oxidant by a plethora of mechanisms. Factors determining its bimodal activity were studied, and the frequencies of their occurrence in the literature were depicted in percentage. Conclusion: The data validates the role of Vitamin C as an antioxidant under physiologic conditions exhibiting a cross over role as a pro-oxidant in pathological conditions. Further studies are required to substantiate its pro-oxidant activity to draw concrete conclusions.